The case of regulation of mobile money in Malaŵi : law and practice - Madise, Sunduzwayo (2017)
The emergence of mobile money and other new forms of payment has changed the sovereign foundations of money. Starting as a DFID funded project in Kenya, mobile money has now spread to many countries including Malaŵi. This thesis looks at the regulatory issues that mobile money poses, and the risks that this alternative form of payment poses to the financial system. The thesis argues that the traditional regulatory architecture of supervising the financial services is ill-suited to supervise mobile money. There are essentially two models of mobile money: telco-led and bank-led. The first is an innovation by telecommunication operators and utilises the small messaging service. There is no requirement to own a bank account. The bank-led model is linked to a bank account. The regulatory approaches to these two models are different. Unlike the telco-led, the bank-led model is under prudential regulation. This has manifested itself in the way the services have developed. The telco-led model had thrived while the bank-led model has fizzled indicating that for mobile money, less regulation may be an enabler. Mobile money is now considered a key developmental tool to achieve financial inclusion among the poor, rural based, unbanked, and underbanked. As opposed to traditional additive forms of financial inclusion, mobile money, especially the telco-led, is transformative. It employs a different approach where the consumer does not have to have a bank account or even travel to a bank to access financial services. In Malaŵi, the financial regulatory framework largely embodies the command and control model. Mobile money, however has largely been regulated using light-touch, with regulation following innovation. This thesis proposes an approach based on the concept of really responsive regulation. This approach, is best suited to embrace mobile money as it passes through the different phases of its evolution.